Anna Christiana Maiorano. (2023). Il corpo grafico di una architettura decorata. Rilievo Disegno Ornamento. Firenze: Altralinea Edizioni (diségno, 2023)
Although Christiana Maiorano’s book can be considered a monographic work entirely dedicated to a specific case study, it is part of a broader research framework related to the knowledge of the architectural, cultural and typological features of the Apulian cities and territory, on which the research group of the Department of Architecture, Construction and Design (ArCoD) of the Politecnico di Bari, to which the author belongs, has been working for a long time. [read more]